Hemodynamic Comparison between modified saddle block and subarachnoid block for Transurethral Resection of Prostate - Anjum, Waqas; Zareen, Abeera; Siddique, Faisal; Anwar, Muhammad Haroon; Rehman, Abdul (Journal of Rawalpindi Medical College, 2023)
BACKGROUND: Spinal anesthesia is often the mode of anesthesia in transurethral resection of prostate (TURP) albeit with risk of hypotension. However, hemodynamic derangement is often less pronounced in saddle block. This study was conducted to compare the mean fall in Mean arterial Pressure (MAP) and Heart rate (HR) between modified saddle block and subarachnoid block for TURP. OBJECTIVE: To compare the mean fall in MAP and HR between modified saddle block and subarachnoid block for TURP. METHODS: In this randomized controlled trial 120 patients undergoing elective TURP were included and divided into two groups. Group A Patients received subarachnoid block and Group B received modified saddle block. Baseline hemodynamics were recorded before and then at 5 minutes after anesthesia. All the collected data was entered into SPSS version 22 and analyzed. Quantitative data like age, BMI, ASA-PS score, duration of surgery and baseline hemodynamics were presented as means and standard deviations. The fall of mean arterial pressure (MAP) & heart rate (HR) were compared among groups by independent t test and P value < 0.05 was considered as statistically significant. RESULTS: Mean fall in MAP was 8.98±1.28 mmHg and 3.13±0.68 mmHg (p<0.001) in group A and B, respectively. Mean fall in HR was 7.17±0.98 and 2.78±0.59 (p<0.001) in group A and group B, respectively. CONCLUSION: Modified saddle block resulted in significantly decreased fall in MAP and HR as compared with subarachnoid block for TURP. KEY WORDS: Modified Saddle Block; Subarachnoid Block; Mean Arterial Pressure